Coaxial Micro Ring Arrays Fabricated on Self‐Assembled Microtube Cavities for Resonant Light Modulation. Issue 9 (1st July 2022) - Saggau, Christian N.; Valligatla, Sreeramulu; Wang, Xiaoyu; Dong, Haiyun; Ma, Libo; Schmidt, Oliver G.
Abstract: Composite optical microcavities, as a versatile platform for light manipulation, have been theoretically revealed that the configuration of concentrically coupled resonant trajectories can significantly enhance the coupling strength, which is however challenging in experimental preparation. Here coaxial whispering gallery resonator chains were designed and fabricated with optically coupled modes split apart by more than the free spectral range (FSR) of the cavity itself. Because such three dimensional (3D) coupled optical systems are extremely difficult to obtain with traditional processing techniques an approach is developed to release and roll‐up pre‐strained, nanostructured silicon nitride membranes into microtubular optical cavities. Parallel nano‐ridges modified on the patterned membranes form into coaxial micro ring arrays after the membrane rolls up into a microtubular structure. Energetic degeneracy, as a consequence of mode splitting exceeding the FSR, leads to interference between bonding and antibonding modes with different mode identities (mode number), resulting in novel light modulation in the form of hybrid super wave modes, which display a distinct hopping behavior resembling linear stretch modes of an oscillator chain. Abstract : Coaxial coupled photonic molecule chains are fabricated by self‐assembly of planar structured waveguides into parallel ring chains. The formed resonant modes show a mode‐splitting exceeding the FSR of the cavity. At the crossing points between resonances of different orders hybrid super wave modes are revealed. They show characteristic field profiles, due to inference of the participating modes.